Bahasa Inggris - Sari, Anna Stasya Prima; Dewi Anzelina (EDUJ : English Education Journal, 2024)
This is Classroom Action Research (henceforth, CAR) which was mainly carried out to prove that the implementation of Make A Match technique could enhance students’ mastery on phrasal verbs and to describe the students’ responses towards the implementation of Make A Match technique in learning processes of phrasal verbs. This CAR was carried out in two cycles in which each cycle consisted of four phases. The research subjects of this CAR are the fourth semester students of the English Language Education Study Program in the Academic Year of 2022/2023 at a private university in Medan consisting of 14 students. The analysis of quantitative data shows that the students’ total score and mean increased continually from the pre-test, formative test, and post-test. The students’ total score in the pre-test is 270 and the mean of the pre-test is 19.3; the students’ total score in the formative test is 792 and the mean of the formative test is 56.6; the students’ total score in the post-test is 1.072 and the mean of the post-test is 76.6. The analysis of qualitative data shows that the learning processes of phrasal verbs through the application of Make A Match technique ran very well. The class atmosphere was more alive and enjoyable after Make A Match technique was implemented so that the students were more active and motivated to learn and master phrasal verbs. It is advisable that English teachers or English lecturers apply Make A Match technique to teach phrasal verbs to their students.